Dampak Pola Asuh Orang Tua Terhadap Keberfungsian Sosial Anak Disabilitas Netra - Karina Silvani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Parents have an obligation to guide, protect and raise their children. So that the role of parents is the main basis in improving social functioning, especially for children with visual disabilities. Children with visual disabilities have unique challenges in improving their social functioning. This research explains three types of parenting, namely, authoritarian, democratic and permissive. So if parents choose the wrong parenting style, it will have an impact on the development process, from this parenting style that helps children with visual disabilities can overcome obstacles and improve strong skills because the role of parents is key in helping their children overcome life's challenges so that they can develop optimally. This study aims to determine the parenting patterns applied by parents to children with visual disabilities, to determine the parenting patterns applied to improve the social functioning of children with visual disabilities, and to determine and improve the social functioning of children with visual disabilities.